2020
DOI: 10.1089/can.2018.0070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Breath and Plasma Tetrahydrocannabinol Concentration Trends Postcannabis Exposure in Medical Cannabis Patients

Abstract: The legalization of cannabis in Canada brings novel challenges across various fronts, such as policy development, law enforcement, and public health and safety. It is imperative to improve our understanding of the mechanisms and trends surrounding cannabis use to develop efficacious methods of tackling these challenges. Materials and Methods: Patients' breath collection was achieved using the ExaBreath device from SensAbues. THC measurements in plasma and breath samples were processed and analyzed using LC-MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 12 publications
(11 reference statements)
5
43
1
Order By: Relevance
“…A positive test result using the two-point breath and one-point blood test indicates that a subject has used cannabis recently through inhalation, i.e., smoking or vaping, and that they are within the three-hour impairment window. Interestingly, approximately 68% of these subjects had detectable levels of Δ 9 -THC in their breath at baseline prior to smoking, in agreement with recent reports by Lynch et al [10] and Olla et al [11]. This nding suggests that the mere presence of Δ 9 -THC in breath does not conclusively demonstrate recent use within the impairment window, which could prove to be a major short-coming of the commercial cannabis breathalyzers currently in development.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A positive test result using the two-point breath and one-point blood test indicates that a subject has used cannabis recently through inhalation, i.e., smoking or vaping, and that they are within the three-hour impairment window. Interestingly, approximately 68% of these subjects had detectable levels of Δ 9 -THC in their breath at baseline prior to smoking, in agreement with recent reports by Lynch et al [10] and Olla et al [11]. This nding suggests that the mere presence of Δ 9 -THC in breath does not conclusively demonstrate recent use within the impairment window, which could prove to be a major short-coming of the commercial cannabis breathalyzers currently in development.…”
Section: Discussionsupporting
confidence: 87%
“…Out of a total of 34 evaluable subjects, (67.6%) had detectable Δ 9 -THC in their breath at base-line prior to smoking (Table 1), which is consistent with recent reports by Lynch KL et al [10] and Olla P et al [11] showing 100% pre-smoking detection rates of D 9 -THC in breath in separate 20-subject and 23-subject studies, respectively. This nding provides further evidence that D 9 -THC cannot be solely relied upon as an indicator of recent cannabis use through inhalation within the impairment window.…”
Section: Baseline Detection Of δ 9 -Thc and Other Cannabinoids In Exhaled Breathsupporting
confidence: 89%
See 1 more Smart Citation
“…Finding an objective measure of recent cannabis use that correlates with impairment has proven to be an elusive goal. In the United States, where the recreational use of cannabis has been legalized in 18 states and Washington, D.C. as of early 2022, some of these states have resorted to setting per se legal limits for D 9 -tetrahydrocannabinol (D 9 -THC) concentrations in blood, limits above which test subjects are considered to be legally impaired. For example, Illinois, Montana, and Washington have established a per se limit of 5 ng/mL, while Nevada and Ohio use a limit of 2 ng/mL [1].…”
Section: Introductionmentioning
confidence: 99%
“…In Colorado, a 5-ng/mL permissible inference standard is employed [1], meaning that a jury can legally presume that subjects testing at or above this level were impaired, unless evidence to the contrary can be provided by the defense. Published research in the last several years, however, has shown that there is no clear relationship between speci c blood or oral uid concentrations of D 9 -THC and impairment [2][3][4][5]. In other words, there is currently no scienti c justi cation for the use of per se legal limits for D 9 -THC blood concentrations, leaving cannabis users in these states at risk of being wrongfully prosecuted for driving under the in uence (DUI) of cannabis.…”
Section: Introductionmentioning
confidence: 99%